ASSESSING THE VIABILITY OF BLOCKCHAIN TECHNOLOGY FOR SUPPLY CHAIN MANAGEMENT: A CASE STUDY APPROACH (CAHIERS MAGELLANES-NS, 2024)
The integration of blockchain technology into supply chain management has garnered significant attention due to its potential to enhance transparency, traceability, and efficiency. This research paper explores the viability of blockchain technology for supply chain management through a case study approach. By analyzing real-world implementations across various industries, the study aims to identify the benefits, challenges, and critical success factors associated with blockchain adoption. Key findings highlight the improved accuracy in inventory management, reduction in fraud, and enhanced collaboration among stakeholders. However, challenges such as high implementation costs, scalability issues, and regulatory concerns persist. The paper concludes with recommendations for organizations considering blockchain technology to improve their supply chain processes, emphasizing the importance of strategic planning, stakeholder engagement, and continuous innovation.